2012
DOI: 10.1242/dmm.009407
|View full text |Cite
|
Sign up to set email alerts
|

High-fat-diet-induced obesity causes an inflammatory and tumor-promoting microenvironment in the rat kidney

Abstract: SUMMARYObesity and concomitant comorbidities have emerged as public health problems of the first order. For instance, obese individuals have an increased risk for kidney cancer. However, direct mechanisms linking obesity with kidney cancer remain elusive. We hypothesized that diet-induced obesity (DIO) promotes renal carcinogenesis by inducing an inflammatory and tumor-promoting microenvironment. We compared chow-fed lean Wistar rats with those that were sensitive (DIOsens) or partially resistant (DIOres) to D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 49 publications
1
52
0
1
Order By: Relevance
“…[43][44][45] Particularly, pervious researches have suggested that excess intake of fat-rich diet may cause hyperlipemia and intestinal endotoxemia, resulting in blood lipid metabolism disorder and systemic inflammation, ultimately contributing to the development of CKD and NAFLD. [46][47][48] Thus, kidney disease caused by eating habits has widely received enough attention by the researchers. HFD-induced metabolic abnormalities would change kidney-related gene expression …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[43][44][45] Particularly, pervious researches have suggested that excess intake of fat-rich diet may cause hyperlipemia and intestinal endotoxemia, resulting in blood lipid metabolism disorder and systemic inflammation, ultimately contributing to the development of CKD and NAFLD. [46][47][48] Thus, kidney disease caused by eating habits has widely received enough attention by the researchers. HFD-induced metabolic abnormalities would change kidney-related gene expression …”
Section: Discussionmentioning
confidence: 99%
“…48 Therefore, inhibition of metabolic disorder at an early stage is considered a feasible strategy for curing chronic renal disease. Recently, quercetin, a beneficial bioflavonoid thought to promote health, has been shown to aid in the prevention of cancer, hepatitis, atherosclerosis, organic lesions, and other diseases.…”
mentioning
confidence: 99%
“…glomerular hypertrophy, glomerular basement membrane thickening, mesangial matrix expansion, and increased tubular inflammation) [83,84]. Together with renal inflammation [85] and oxidative stress [86], these changes may lead to decreased renal function and ultimately glomerulosclerosis and tubulointerstitial fibrosis [78,[87][88][89].…”
Section: Ecbs and Obesity-related Kidney Dysfunctionmentioning
confidence: 99%
“…d-Galactose has been used to induce oxidative stress in vivo to mimic the natural aging process in rats and mice (17)(18)(19)(20). In addition, a high-fat diet (HFD) was found to be a significant risk factor for kidney disease (21)(22)(23). HFD-induced obesity may expedite the aging process (24).…”
Section: J Nutr Scimentioning
confidence: 99%